Mitochondrial ribosomal proteins: potential targets for cancer prognosis and therapy - Zhu, Jianqing; Wen, Na; Chen, Wen; Yu, Haotian (Frontiers in Oncology, 2025)
Mitochondrial ribosomal proteins (MRPs) are essential components of mitochondrial ribosomes, responsible for translating proteins encoded by mitochondrial DNA and maintaining mitochondrial energy metabolism and function. Emerging evidence suggests that MRPs exhibit significant expression changes in multiple cancer types, profoundly affecting tumor biology through modulating oxidative stress levels, inducing metabolic reprogramming, disrupting cell cycle regulation, inhibiting apoptosis, promoting mitophagy, and remodeling the tumor microenvironment. Specifically, MRPs have been implicated in tumor cell proliferation, migration, invasion, and apoptosis, highlighting their potential as therapeutic targets. This review summarizes the multifaceted roles of MRPs in cancer, focusing on their impact on the tumor microenvironment and their potential as prognostic biomarkers and therapeutic targets. We also explore the implications of MRPs in precision oncology, particularly in patient stratification and the design of metabolic targeted therapies, offering new insights and research directions for the precise prevention and treatment of cancer.